Continuous induction with lenalidomide/dexamethasone versus autologous stem cell transplantation in newly diagnosed multiple myeloma: a case for response-adapted approach. Issue 9 (29th July 2022) - Lahoud, Oscar B.; Landau, Heather; Nguyen, James; Devlin, Sean; Lendvai, Nikoletta; Weltz, Jonathan; Ayorinde, Tumininu; Chung, David J.; Lesokhin, Alexander M.; Kewalramani, Tarun; Korde, Neha; Mailankody, Sham; et al.
Abstract: Although upfront autologous stem cell transplantation (ASCT) generally improves progression-free survival (PFS) in newly diagnosed multiple myeloma (NDMM), the overall survival (OS) benefit and optimal timing of ASCT are not well established. Patients with early response may be able to safely continue induction and avoid ASCT without compromised outcomes. We report an extended follow-up analysis of a phase 2 trial that randomized transplant-eligible patients with NDMM who responded to induction (50/65 patients) to continued induction or ASCT; median follow-up was 8.0 years. Patients had similar 8-year PFS (55% vs. 43%), 8-year OS (83% vs. 72%), and rates of at least very good partial response (72% vs. 84%) whether continuing induction of lenalidomide and dexamethasone (Ld arm) or receiving ASCT (Ld + ASCT arm) ( p  = 0.5). Notably, over 50% of patients receiving continuous Ld had PFS of 5–10 years. These results suggest the need for prospective trials incorporating response-adapted therapeutic approaches to NDMM. STATEMENT OF PRIOR PRESENTATION: Presented in abstract form (interim analysis) at the 56th annual meeting of the American Society of Hematology (San Francisco, CA, 6 December 2014) and at the 57th annual meeting of the American Society of Hematology (Orlando, FL, 3 December 2015).